Formation of State System of Geological Exploration and Development of Yakutia Mineral Deposits (1920-1925) - N. I. Burnasheva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The first initiatives of the Soviet authorities on the organization of geological researches of minerals and creation of the enterprises for their industrial production in Yakutia are considered. It is established that in the process of formation of the state system of geological exploration and development of subsoil resources in Yakutia there are two main periods: the initial one (1920-1922), when the search for minerals was not yet associated with the industrial development of deposits, and the second period (1923-1925), during which the state system of search, exploration and development of mineral deposits was created in the Yakut ASSR, at the same time, the centralized structure of industry management included for the first time both regulatory bodies for geological prospecting and exploration of minerals, and bodies for managing enterprises of industrial field development. The author argues that as a result of the reforms of 1920-1925, geological exploration, which previously was primarily purely scientific in nature, was put at the service of production. It is concluded that in these years the Yakut ASSR formed a centralized state management structure that controlled the process of technical and economic evaluation of mineral deposits and the implementation of all targeted activities in the field of mining.